Using self-phase modulation for temporal compression of intense femtosecond laser pulses. (August 2017) - Mironov, S.Yu.; Ginzburg, V.N.; Yakovlev, I.V.; Kochetkov, A.A.; Shaykin, A.A.; Khazanov, E.A.; Mourou, G.A.
Abstract: We report a theoretical analysis of the spectrum broadening of intense chirped femtosecond pulses in media with cubic nonlinearity. Subsequent temporal compression of such pulses using a quadratic spectral phase corrector is investigated. Pulse compression from 57 fs to 22 fs is demonstrated experimentally in a petawatt laser beam.